畢氏定理 證明 1

\begin{equation}\because\triangle\mathrm{ACB}\sim\triangle\mathrm{AHC}\end{equation}

\begin{equation}\therefore\mathrm{b}:(\mathrm{c}-\mathrm{x})=\mathrm{c}:\mathrm{b}\end{equation}

\begin{equation}\Rightarrow\mathrm{b}^2+\mathrm{cx}=\mathrm{c}^2\cdots\cdots(\mathrm{1})\end{equation}

\begin{equation}\because\triangle\mathrm{ACB}\sim\triangle\mathrm{CHB}\end{equation}

\begin{equation}\therefore\mathrm{a}:\mathrm{x}=\mathrm{c}:\mathrm{a}\end{equation}

\begin{equation}\Rightarrow\mathrm{a}^2=\mathrm{cx}\cdots\cdots(\mathrm{2})\end{equation}

\begin{equation}將(\mathrm{2})代入(\mathrm{1})可以即可得到\end{equation}

\begin{equation}\Rightarrow\mathrm{a}^2+\mathrm{b}^2=\mathrm{c}^2\end{equation}

Reference:

1. Elisha S. Loomis (1935): « The Pythagorean Proposition ». p. 40.

發佈留言